Take care : how to be a great employer for working carers - Grayson, David, 1955- (Emerald Publishing Limited, 2017)
There could be as many as 300 million caregivers in the global workforce providing care for loved ones - elderly parents, a life-partner with a health condition, or a disabled child/sibling or close friend who needs support. As populations age around the world and welfare support declines, the number of people voluntarily caring for another will grow. However, despite the demands and pressures that caregivers are under, many organisations offer little practical support to employees - support that, if provided correctly, will benefit both employee and employer. Take Care is a practical guide that enables employers to better understand and support employees with caring responsibilities. It presents this as part of good management practice that strengthens organizational resilience and sustainability, and also argues that this is now an integral element of being a responsible employer and organisation. The book includes practical examples from more than fifty employers around the world, from small businesses to global enterprises, as well as public sector and NGO examples. It also features the personal stories of individuals in the workplace who have successfully championed change.- Resumé vydavatel
Obsahuje index.
Keywords: pečovatelé; domácí péče; care workers; home care; příručky; elektronické knihy; handbooks and manuals; electronic books